2022
DOI: 10.1515/med-2022-0577
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous treatment of a pubovesical fistula and lymph node metastasis secondary to multimodal treatment for prostate cancer: Case report and review of the literature

Abstract: Pubovesical fistula (PVF) is a rare complication of radical treatments for prostate cancer (PCa), especially when a multimodal approach is performed. We present a case of PVF with extensive communication between the bladder and the pubic bones, and lymph node metastases of PCa treated by cystectomy and salvage lymphadenectomy. We describe a case of a 65-year old male patient who, after radical prostatectomy and adjuvant radiation therapy, suffered from suprapubic and perineal pain, ambulation difficulties and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The most frequent postoperative complications described in the literature are bleeding with pelvic hematoma, urinary leakage, lymphocele, small bowel obstruction, port-site hernia, bladder neck contracture, and thromboembolic complications. Peri-and postoperative complications in RARP have been reported by Novara et al to range from 3% to 26%, while in a review by Sotelo et al, they have been found to range between 1.9% and 6.8% (23,29). In a recent meta-analysis by Pucheril et al, the median rate of overall complications was found to be 12.6% but with wide ranges in single studies; in any case, most complications were of minor grade (24).…”
Section: Discussionmentioning
confidence: 96%
“…The most frequent postoperative complications described in the literature are bleeding with pelvic hematoma, urinary leakage, lymphocele, small bowel obstruction, port-site hernia, bladder neck contracture, and thromboembolic complications. Peri-and postoperative complications in RARP have been reported by Novara et al to range from 3% to 26%, while in a review by Sotelo et al, they have been found to range between 1.9% and 6.8% (23,29). In a recent meta-analysis by Pucheril et al, the median rate of overall complications was found to be 12.6% but with wide ranges in single studies; in any case, most complications were of minor grade (24).…”
Section: Discussionmentioning
confidence: 96%